Promotion of "Generative Places" based on Municipal economic and financial sustainability - Emília Malcata Rebelo (2015)
The research reported in this article aims at assessing how territorial management instruments appliedat the municipal level can allocate for the social interest the land unearned increments that stem frompublic decisions concerning the implementation of territorial plans and/or changes in land uses or landuse intensities.If, on the one hand, the characteristics of the physical spaces that result from public, private and/orcommunity decisions set the conditions for local peoplesŽ everyday life, the municipality shall vesteconomic and financial sustainability conditions that are able to support peoplesŽ quality of life, on theother. Thus territorial management instruments applied at the local level shall be able to manage thephysical, social and cultural spaces in a balanced way. And to pursue this goal, these instruments shallbe designed to recover the land unearned increments engendered by public decisions that, instead offinishing at private landowners hands, should better go back to that municipalityŽs population.So the new territorial management instrument herein proposed consists in charginglandowners/promoters a 20% fee on land surplus-values that result from the assignment by urban plansof specific building capacities to certain urban interventions. The proposed methodology is applied tothe Urban Development Plan of the Planning Unit 11 of the municipality of Lagoa, located in the Algarve,Portugal.This new territorial management instrument may be easily applied to other municipalities, within thescope of the application of different kinds of urban plans. It ensures that the surplus-values theyengender are pointed to social purposes. And it further supports municipal economic and financialsustainability based on a strategic and integrated planning perspective.